The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/gene.2008.19
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the functional relevance of a putative regulatory SNP of PDCD1, PD1.3, associated with systemic lupus erythematosus

Abstract: This study aimed to test the functional effects of the PD1.3 single nucleotide polymorphism (SNP) (rs11568821), which were proposed based on its association to systemic lupus erythematosus (SLE) susceptibility and in electrophoretic mobility shift assays (EMSA) results. We analysed transcriptional effects of the PD1.3 locus by enhancer reporter assays. Results were against the hypothesis that the PD1.3 locus acts as enhancer in transcriptional regulation of PDCD1. In addition, they excluded a differential effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
8
3
1
Order By: Relevance
“…PDCD1 binds to its ligands, including PD‐L1 and PD‐L2, then recruits protein tyrosine kinases, which produces a coactivated effect that is necessary for inhibition of the dysimmunity reaction. A recent study reported that the anomalous connection of RUNX1 and the PDCD1 single nucleotide polymorphism PD1.3 is essential to the pathogenesis of systemic lupus erythematosus (SLE) 21 . We did not find significant difference in mRNA expression of PDCD1 between the psoriasis and control groups.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…PDCD1 binds to its ligands, including PD‐L1 and PD‐L2, then recruits protein tyrosine kinases, which produces a coactivated effect that is necessary for inhibition of the dysimmunity reaction. A recent study reported that the anomalous connection of RUNX1 and the PDCD1 single nucleotide polymorphism PD1.3 is essential to the pathogenesis of systemic lupus erythematosus (SLE) 21 . We did not find significant difference in mRNA expression of PDCD1 between the psoriasis and control groups.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent study reported that the anomalous connection of RUNX1 and the PDCD1 single nucleotide polymorphism PD1.3 is essential to the pathogenesis of systemic lupus erythematosus (SLE). 21 We did not find significant difference in mRNA expression of PDCD1 between the psoriasis and control groups.…”
Section: Our Resultscontrasting
confidence: 53%
“…Based on their model, patients who carry this allele may have a lower expression of PD-1 molecule in activated lymphocytes, and could have a better response to IFN-a stimulation. However other authors, using a luciferase reporter assays, showed that the two alleles of PD-1.3 have similar effects on reporter gene transcription [39]. In spite of the possible implication of this polymorphism in the regulation of protein expression, this study clearly showed that PD-1.3 modulated the outcome to treatment for HCV infection treatment.…”
Section: Discussioncontrasting
confidence: 68%
“…The mechanistic link between PD-1 or PD-L1 expression and the pathogenesis of human SLE is not well understood. Polymorphisms in the PD-1 gene are associated with SLE susceptibility in some populations of adults and children1112131415. However, PD-L1 gene polymorphisms were not associated with SLE1617.…”
mentioning
confidence: 98%